MENINGKATKAN KARAKTER KERJASAMA ANAKMELALUI BERMAIN BALOK USIA 4-5 TAHUN DI TAMAN KANAK-KANAK PUSAKA INDAH KARANG PACI SAMARINDA TAHUN AJARAN 2018/2019 - Amy - Puspita; Rizqy - Syafrina (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2019)
This research is to improve the Character of Child Cooperation through playing blocks aged 4-5 years in the Pusaka Indah Karang Paci Samarinda Kindergarten 2018/2019 Learning Year which is conducted on children aged 4-5 years, totaling 16 children. The research was conducted in 2 cycles, starting with the pre-cycle, the first cycle, the second cycle each carried out as much as 2 meetings with 2 times the learning process. Data analysis techniques use qualitative description analysis, which is a research method that is describing reality or facts in accordance with the data obtained. The results of the research in each cycle can be seen as follows, This can be seen from the results of the pre-cycle average value obtained 24.47%, classified as Not Developing, in the first cycle increased an average of 33.80%, classified as Starting Developing, and at the second cycle increased again with an average of 56.73% classified as Developing as Expected. From the results of this study in each of the above cycles, it can be said that the use of beams can improve the cooperation character of children aged 4-5 years. Based on the results of the study that through playing the beam can improve the collaboration character of children aged 4-5 years in the Karang Paci Samarinda Heritage Park. With the implementation of this class it is hoped that schools, especially teachers, will use this method because the method of playing beams can improve the character of child collaboration.